Phosphate fertilization in processing tomato irrigated by localized irrigation systems - Silva, Cicero José da; Silva, Luiz Felipe Mariano da; Neres, Jeferson dos Santos; Golynski, Adelmo; Pontes, Nadson de Carvalho; Moraes, Emmerson Rodrigues de; Megguer, Clarice Aparecida (Comunicata Scientiae, 2024)
The aim of this work was to evaluate different combinations of phosphate fertilizer sources on processing tomato (cv. BRS Sena) development and yield, irrigated by localized irrigation systems. The experimental design was in randomized blocks, in split plots, in a factorial scheme (3x5), with four replications. In the plots were used three irrigation systems: drip; subsurface drip and microsprinkler. In the subplots, five combinations of phosphate fertilizer: 100% of Thermophosphate; 100% Triple Superphosphate; 75% Thermophosphate + 25% Triple Superphosphate; 50% Thermophosphate + 50% Triple Superphosphate; and 25% Thermophosphate + 75% Triple Superphosphate. At harvest, the yield of green, ripe and rotten fruits; total yield; percertation of green, ripe and rotten fruits; firmness; pH; titratable acidity; total soluble solids; and fruit size and density were evaluated. Fertilization with Thermophosphate, or its association with Triple Superphosphate, is beneficial for tomato yield. Microsprinkler irrigation provides higher percentage of ripe fruits and lower incidence of green fruits and, when associated with phosphate fertilization of 100% of Thermophosphate, promotes higher yield. Drip and subsurface drip irrigations proved ineffective for the tomato when all the planting fertilization was concentrated in the planting groove. Phosphate fertilization with only Triple Superphosphate was not beneficial the yield, regardless of the irrigation system used. Fertilization with Triple Superphosphate alone or associated with Thermophosphate favored the concentration of maturation, total soluble solids content and tomato fruit acidity.